Penerapan Model Pembelajaran Projek Based Learning dengan Pendekatan STEM terhadap Antusias Siswa Jurusan Akuntansi Fase E pada Mata Pelajaran Informatika di SMK Negeri 3 Surakarta - Anas, Rizky Chairul; Liantoni, Febri; Maryanti (Indonesian Journal of Learning and Instructional Innovation, 2024)
Learning is a collaboration between teachers and students to share and process information. The teacher has an crucial role in the learning process as a designer of learning scenarios, so that an interesting teaching and learning process occurs and can increase student enthusiasm. The results of observations found a lack of student enthusiasm in informatics subjects. This is characterized by the lack of interaction between students and teachers, lack of focus on learning, some students are busy playing their own gadgets and the lack of students to ask questions while learning. The learning that took place before was boring using only the lecture and question and answer technique, and the lack of utilization of the facilities provided. This study seeks to explore the implementation of the project-based learning model with a STEM approach in Informatics subjects to gauge student motivation. The utilized research methodology was class action research. The research participants comprised were 35 students of phase E of the Accounting Department at SMK Negeri 3 Surakarta. The data collection method used teacher observation sheets and learning outcomes tests. The observation revealed a high category, reaching a score of 66% in the first meeting, 77% in the second meeting and 77% in the third meeting. These results are also supported by an increase in the class average score by 20%. Based on these findings, it can be iferred that the implementation of the Project Based Learning model with the STEM Approach can increase student enthusiasm.